Un/learning Habituation of Body-Mind Binary through the Teaching- Learning Body/Mind - Jeong-eun Rhee; Stephanie L. Curley; Sharon Subreenduth (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
A complex critique of how society constructs women of color in the academy combines with deeply personal interludes and a polyphony of scholarly voices to demonstrate ways that their objectified bodies can not only resist but also improvise as they question what it means to be different.